The Development of Fotonovela Learning Media Assisted by Ms Publisher on Arithmetic Sequence and Progression - Ika Mareta; Dafik Dafik; Randi Pratama Murtikusuma (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
This research aims to (1) describe the process of developing a fotonovela learning media by using Ms Publisher on arithmetic sequence and progression, (2) to know the results of developing learning media Ms Publisher on arithmetic sequence and progression. Online learning media allows students to access information quickly and more efficiently. This research was processed through the stages of 4D that are define, design, develop, and disseminate. Development research results a product is tested validity, practically, and effectiveness. The research instruments used were questionnaire for needs analysis, validation sheets, test, and student response questionnaire. The subjects of the test were 34 students of XI MIPA 4 SMAN 1 Tempeh. The media validation includes three aspects, namely materian and question aspects, content aspects, and language aspects.The result of fotonovela validation including valid criteria with an average of 3,67. Then the effectiveness of media on students learning outcomes included in high level of effectiveness with percentage 88,24%. While the criteria of fotonovela media practicity gets the percentage of student response by 85,23% which is included in high criteria.